PERAN PUSTAKAWAN DALAM PENINGKATAN JASA LAYANAN PEMUSTAKA DI DINAS PERPUSTAKAAN KOTA PONTIANAK - Jariah, Ainun; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was backgrounded by the researcher’s interest in doing an observation on the role of the librarians in improving library service at the city library of Pontianak, This study was backgrounded by the researcher’s interest in doing an observation on the role of the librarians in improving library service at the city library of Pontianak, the researcher wants to know whether the librarian has played a role in improving existing service . This study aims to describe the roles and stages of librarians in improving their services. The study was carried out by applying the descriptive method using the qualitative approach, what efforts have been made by librarian to improve their sevices. The techniques data collection used were observation, interviews, and documentation. The librarian, staff, and visitors took part in the interviews. The findings show that the role of the librarians in conducting the services has been well-improved, observation is research looking directly to the location for obtaining information. However, the difficulties faced are the lack of library staff and the room that do not fully support library activities.Keyword: Role of Librarians, Library Service, Visitors